Crowdocracy : the end of politics - Watkins, Alan.; Stratenus, Iman (Kent, 2016)
Crowdocracy : The End of Politics discusses one of the world's most debated and critical issues - who decides our future and how should we be governed? If a political party receives a tenth of all votes but no representation in government, can we claim the system is democratic and people's voices are being heard? Should an international political body, bank or committee be able to decide the destiny of a country and its government? It is clear that democracy is struggling, political representatives seemingly more inclined to pursue their own ambitions than proactively address the challenging issues facing society. But is there any alternative and can we chart a wiser way forward? Most national populations feel disenfranchised with the political process and largely powerless to make any real difference themselves. Crowdocracy offers a radical new way forward, one that allows all of us - not just some of us - to participate in how we are governed. It offers a compelling examination of the contemporary relationships between people and politics. Crowdocracy suggests a new model for how people can decide their own future, create a new political landscape, and ultimately shape and govern their communities. Crowdocracy is the second title in the ground-breaking Wicked & Wise series, a range of topical books that explore hotly debated and 'wicked' issues facing the planet and its people, offering intelligent, challenging and 'wise' ways forward that may be able to break through existing intractable positions. Each book in the series is co-authored by renowned leadership consultant Alan Watkins and an eminent thinker in each subject field.
Keywords: Politics and culture